THE SIGNIFICANCE OF EUHEDRAL CALCIC PLAGIOCLASE INCLUSIONS IN GARNET FROM THE LUTZOW-HOLM COMPLEX, EAST ANTARCTICA : A TEXTURAL INDICATOR OF PARTIAL MELTING IN PELITIC GNEISSES - ヒロイ, ヨシクニ; モトヨシ, ヨウイチ; シライシ, カズユキ /; HIROI, Yoshikuni; MOTOYOSHI, Yoichi; SHIRAISHI, Kazuyuki; ELLIS, David J. (National Institute of Polar Research, 1995)
P(論文) Calcic, faceted plagioclase inclusions occur commonly within garnet porphyroblasts in upper amphibolite to granulite facies pelitic rocks of the Early Paleozoic Lutzow-Holm Complex, East Antarctica, as is also the case in high grade pelitic metamorphics worldwide. That euhedral plagioclase crystals are only preserved as inclusions in garnet and not in the matrix of these rocks is due to the rigid nature of garnet protecting inclusions from later deformation and recrystallization. The occurrence may have resulted from a partial melting reaction as follows-Biotite+sillimanite+sodic plagioclase+K-feldspar+quartz±H_2O=granitic melt+garnet+more calcic plagioclase+ilmenite (or rutile). Thus euhedral plagioclase is a potential indicator of partial melting during high temperature metamorphism. departmental bulletin paper